Analysis Of Digital-Based Sharia Banking Services On Customer Experience : A Case Study Of BSI KCP Probolinggo Brak - Rofa Lailatul Hasanah; Moh. Abd Rahman; Hayatul Millah (International Journal of Management and Business Economics, 2026)
This study aims to analyze the form and quality of digital-based Islamic banking services and customer experiences in using these services. It also examines the factors influencing customer experiences in the context of digital Islamic banking. The study employed a qualitative approach with a case study method at Bank Syariah Indonesia (BSI). Data were collected through in-depth interviews, observation, and documentation. The data were analyzed using an interactive model consisting of data reduction, data presentation, and conclusion drawing. The findings show that the BSI Mobile application provides various digital transaction features that improve convenience and efficiency for customers. However, the quality of digital services is not yet fully optimal. Several problems remain, including system disruptions, delayed transaction notifications, and difficulties during account activation. Customer experiences were found to be heterogeneous. Some customers perceived digital services as practical and convenient, while others experienced difficulties due to limited digital literacy and technical barriers. This study further reveals that customer experience in Islamic digital banking is shaped not only by technological and service factors, but also by Islamic values such as trust, transparency, and religious commitment. This finding represents the main novelty of the study by extending the concept of customer experience beyond functional and emotional dimensions toward a religious value dimension within Islamic banking services